Safety of fibula free flap in patients following total knee replacement. Issue 2 (21st October 2020) - Harris, Brianna N.; Ghazizadeh, Shabnam; Bayon, Rodrigo; Kejner, Alexandra E.; Cannady, Steven B.; Greene, Benjamin J.; Huang, Andrew T.; Curry, Joseph; Blackwell, Keith E.; Ducic, Yadranko; Wax, Mark K.
Abstract: Background: Fibula free flap (FFF) is the preferred osteocutaneous flap for reconstruction of large head and neck composite defects. There is a paucity of data whether FFF can be performed safely in patients with knee replacement (total knee arthroplasty [TKA]). Methods: Multi‐institutional review of outcomes following FFF in patients who had prior TKA. Results: Ten surgeons reported successful FFF in 53 patients with prior TKA. The most common preoperative imaging was a CT angiogram of the bilateral lower extremities. There was no evidence of intraoperative vascular abnormality. Physical therapy began between postoperative day 1 to postoperative day 3. At 1 month postoperatively, 40% of patients were using a cane or walker to ambulate, but by 3 months all had returned to baseline ambulatory status. At >1 year, there were no gait complications. Conclusion: FFF appears safe in patients with prior knee replacement without an increased risk of complications compared to baseline.